A Uniquely Targeted, Mobile App-Based HIV Prevention Intervention for Young Transgender Women: Adaptation and Usability Study - Kuhns, Lisa M; Hereth, Jane; Garofalo, Robert; Hidalgo, Marco; Johnson, Amy K; Schnall, Rebecca; Reisner, Sari L; Belzer, Marvin; Mimiaga, Matthew J (JMIR Publications, 2021)
BackgroundYoung transgender women (YTW) are a key population for HIV-related risk reduction, yet very few interventions have been developed to meet their needs. Mobile health interventions with the potential for both efficacy and wide reach are a promising strategy to reduce HIV risk among YTW. ObjectiveThis study aims to adapt an efficacious group-based intervention to a mobile app, Project LifeSkills, to reduce HIV risk among YTW, and to test its acceptability and usability. MethodsThe group-based intervention was adapted to a mobile app, LifeSkills Mobile, with input from an expert advisory group and feedback from YTW collected during user-centered design sessions. A beta version of the app was then tested in a usability evaluation using a think-aloud protocol with debriefing interviews, recordings of screen activity, and assessments of usability via the Post-Study System Usability Questionnaire (PSSUQ) and the Health Information Technology Usability Evaluation Scale (Health-ITUES). ResultsYTW (n=8; age: mean 24 years, SD 3 years; racial or ethnic minority: 7/8, 88%) provided feedback on the app prototype in design sessions and then tested a beta version of the app in a usability trial (n=10; age: mean 24 years, SD 3 years; racial or ethnic minority: 8/10, 80%). Both usability ratings (Health-ITUES: mean 4.59, SD 0.86; scale range: 1-5) and ratings for satisfaction and accessibility (PSSUQ: mean 4.64, SD 0.90; scale range 1-5) were in the good to excellent range. No functional bugs were identified, and all mobile activities were deployed as expected. Participant feedback from the usability interviews indicated very good salience of the intervention content among the focal population. Participants' suggestions to further increase app engagement included adding animation, adding audio, and reducing the amount text. ConclusionsWe conclude that the LifeSkills Mobile app is a highly usable and engaging mobile app for HIV prevention among YTW.